Escharotic agents: a Victorian remedy in the 21st century. (25th January 2022) - Doyle, Claire; D'Arcy, Clare; Ryan, Aisling
Abstract : A 72‐year‐old woman had a warty growth 'burnt off' with a herbal remedy by a local farmer in rural Ireland. We saw the patient a number of years later in clinic and she brought the specimen with her, which was processed by the pathology department. We report her case and some interesting background information regarding escharotic agents.